The EEC in the global system - Lall, K. B., 1915-; Ernst, Wolfgang, Dr.; Chopra, H. S. (Hardev Singh), 1932- (New Delhi : Allied, 1984)
Papers presented at a Jawaharlal Nehru University-EEC joint seminar, New Delhi, November 1980.
Includes bibliographies and index.
Keywords: International economic relations